Literacy Instruction and Self-efficacy in an English as a Foreign Language Learner with Asperger Condition in the Third Grade of a Bilingual School. - Cabrera Quiñonez, Erika Vanessa (2024)
This study aimed to determine that an EFL classroom with a student with Asperger's condition should be fostered in language proficiency in a way that is both supportive and responsive to their unique learning needs. This involves providing tailored instruction that accommodates any challenges the student may face with language processing, social interaction, or sensory sensitivities. The focus should be on enhancing the student's abilities in reading, writing, listening, and speaking, while also building their confidence and reducing anxiety in the learning environment. The data was collected through the use of unstructured observations applied in the reading, vocabulary, and writing, working directly with the student in the language arts classes. The findings showed that the student scored low in each evaluated skill, considering that each test significantly affected his self-efficacy, causing his behavior to be difficult to control when the teacher did not provide techniques and strategies to improve their academic performance, and the actual methodology applied mixed methods and a descriptive design involves integrating both quantitative and qualitative approaches to provide a comprehensive understanding of the research problem. Thus, the mentioned techniques and strategies are to be applied to the student in the classroom to solve the problems found in this research project.